Prevalence and predictors of transfusion-transmitted infections among blood donor types at a teaching hospital in Ghana: Implications for haemovigilance - Alice Charwudzi; Edward Morkporkpor Adela; Kingsley Kwadwo Asare Pereko; Martin Ampofo; Aaron Fenuku; Daniel Edem Azumah; Abdul Raman Asemah; Edward Ahiakwah; Angela Animwaah Osei; Emmanuel Kobina Mesi Edzie (PLoS ONE, 2025)
Introduction Transfusion-transmitted infections (TTIs), notably hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), and syphilis, remain a major threat to blood safety in resource-limited settings. Ghana mainly uses rapid diagnostic tests (RDTs) for initial screening, which may affect the accuracy of detecting TTIs. Objective This study estimated the prevalence, identified sociodemographic and donor-type predictors of TTIs and compared the diagnostic yield of RDTs versus ELISA in a teaching hospital in the Central Region of Ghana. Methods This retrospective study analysed 10,152 available blood donors’ records screened from January 2022 to March 2024. Fixed-site donors were initially screened using RDTs (SD Biosensor Standard Q® HBsAg/HCV Ab, First Response® HIV 1-2.0, Advanced Quality™ Syphilis) followed by confirmatory ELISA testing for RDT-non-reactive samples. Mobile donors underwent ELISA (ChemWell® FUSION analyser) testing only. Multivariable logistic regression was used to identify independent TTI predictors. Results The overall prevalence of TTIs (infection with at least one tested pathogen) was 16.5% (95% CI: 15.80-17.20; N = 1,675), with syphilis 8.4% (95% CI: 7.83-8.91; N = 850) being the most common. Voluntary donors had a lower TTI prevalence than replacement donors (10.6% vs 19.9%, p < 0.001). Repeat donors exhibited reduced risk of HBV (aOR: 0.254, 95% CI: 0.206-0.313, p < 0.001), HCV (aOR: 0.734, 95% CI: 0.568-0.949, p = 0.018), and syphilis (aOR: 0.486, 95% CI: 0.417-0.567, p < 0.001). However, donor type itself was not a significant predictor of TTIs after adjusting for sociodemographic variables. ELISA testing identified an additional 7.3% (95% CI: 6.67-8.01; N = 422/5,754) TTI cases among RDT non-reactive fixed-site donors (missed cases). Conclusion The high prevalence of TTIs highlights persistent blood safety challenges. Repeat donation was independently protective, reducing risks of HBV, HCV, and syphilis. To improve blood safety, it will be essential to encourage regular voluntary donations. It will also require supplementing RDTs with ELISA where feasible, and strengthening haemovigilance systems, while accounting for the cost and logistical constraints. Although NAT is the gold standard for TTI detection, nationwide implementation in Ghana is currently not feasible.